INTEGRATING PANCASILA JUSTICE IN SENTENCING BALINESE CUSTOMARY CRIMES: TOWARD AN INTEGRATIVE MODEL UNDER INDONESIA’S NEW CRIMINAL CODE - Mulyono, Galih Puji; Putri, Ni Luh Putu Alfina; Rifandhana, Raditya Feda; Douglas, Heather (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
This study critically examines the integration of Balinese customary criminal law, specifically the delict of Lokika Sanggraha, within Indonesia’s formal criminal justice system under the recent National Criminal Code (Law Number 1 of 2023). Lokika Sanggraha, codified in Article 359 of the Adhigama Code, addresses cases in which a man engages in sexual relations under a promise of marriage but subsequently abandons the pregnant woman. Historically, the colonial-era Criminal Code lacked provisions for such scenarios, necessitating the judicial incorporation of living law (customary law) to fill normative gaps. The Denpasar District Court Decision Number 997/Pid.Sus/2019/PN Dps exemplifies judicial engagement with customary law, where the court applied the Adhigama Code in conjunction with Emergency Law Number 1 of 1951, resulting in a custodial sentence for the perpetrator. This case illustrates the tension between formal legal codification and living law, highlighting both progressive impulses and limitations in sentencing, notably in addressing the multidimensional harm to victims. Using a combined methodological approach—including statutory, case, and conceptual analyses—this research evaluates the decision through Pancasila justice dimensions, progressive legal theory, restorative justice, and legal pluralism frameworks. It further introduces an Integrative Sentencing Model that operationalizes the principles of proportional punishment, customary obligation fulfillment, victim compensation, and child protection under the National Criminal Code. Comparative analysis with Supreme Court Decision No. 1644 K/Pid/1988 and the codified Sharia-based system of Aceh demonstrates the spectrum of judicial approaches to customary law, informing a hybrid framework that balances formal adjudication with culturally embedded restorative mechanisms. The study concludes that while recognition of living law has advanced constitutionally, effective operationalization requires judicial capacity building, coordination with customary institutions, and robust procedural safeguards to ensure substantive justice. The proposed Integrative Sentencing Model provides a practical roadmap for aligning customary practices with formal legal standards, advancing human rights, gender justice, and restorative outcomes within Indonesia’s pluralistic legal landscape.